Description of a new species of Sphaerosyllis Claparède, 1863 (Polychaeta: Syllidae: Exogoninae) from the Alicante coast (W Mediterranean) and first reports of two other species of Syllidae for the Mediterranean Sea and the Iberian Peninsula - DEL-PILAR-RUSO, Y.; SAN MARTIN, G. (Mediterranean Marine Science, 2012)
During a study aiming at the evaluation of the distribution of the soft-bottom community at different taxonomic scales, the family Syllidae was analysed to the species level. Among the identified material, one undescribed species belonging to the genus Sphaerosyllis Claparède, 1863 was found and two species constitute new reports for the Mediterranean Sea and for the Iberian Peninsula: Parapionosyllis cf. macaronesiensis Brito, Núñez and San Martín, 2000, and Syllis cf. mauretanica (Licher, 1999) n. comb., both only previously known from the subtropical Eastern Atlantic Ocean. The new species of Sphaerosyllis is mainly distinguished in having bulbous, small antennae, tentacular and dorsal cirri, small parapodial glands, with granular material, and compound chaetae with short blades. In this paper, we describe the new species and the specimens of the new reports.